The MUSE QSO Blind Survey: A Census of Absorber Host Galaxies. Issue Volume 11:Issue S321(2015) (21st March 2017) - Straka, Lorrie A.; ,
Abstract: Understanding the distribution of gas in galaxies and its interaction with the IGM is crucial to complete the picture of galaxy evolution. At all redshifts, absorption features seen in QSO spectra serve as a unique probe of the gaseous content of foreground galaxies and the IGM, extending out to 200 kpc. Studies show that star formation history is intimately related to the co-evolution of galaxies and the IGM. In order to study the environments traced by absorption systems and the role of inflows and outflows, it is critical to measure the emission properties of host galaxies and their halos. We overcome the challenge of detecting absorption host galaxies with the MUSE integral field spectrograph on VLT. MUSE's large field of view and sensitivity to emission lines has allowed a never-before seen match between the number density of absorbers along QSO sightlines and the number density of emission line galaxies within 200 kpc of the QSO. These galaxies represent a sample for which previously elusive connections can be made between mass, metallicity, SFR, and absorption.